An investigation into the neuroprotective effects of melatonin in a model of rotenone-induced neurodegeneration - Kadanthode, Rubina John (Rhodes University, Faculty of Pharmacy, Pharmacy, 2004)
Parkinson's disease, one of the most common neurodegenerative disorders associated with ageing, is characterised by abnormal and profound loss of nigrostriatal dopaminergic neurons. The cause of Parkinson's disease is unknown, but epidemiological studies suggest an association with pesticides and other environmental toxins, and biochemical studies implicate oxidative damage and mitochondrial impairment, particularly at the level of complex I enzyme. Recently, rotenone, a commonly used organic pesticide and a classical inhibitor of mitochondrial complex I has been reported to reproduce the specific features of Parkinson's disease in rodents. The mitochondrial respiratory chain is one of the most important sites of reactive oxygen species production under physiological conditions. Toxic free radicals have been implicated in a variety of neurodegenerative diseases as well as ageing itself. Melatonin, a secretory product of the pineal gland is a multifaceted free radical scavenger and natural antioxidant. In the present study, the neuroprotective effects of melatonin against the environmental neurotoxin, rotenone was investigated. Initial studies showed that inhibition of mitochondrial complex I enzyme by rotenone induced superoxide radical generation. Melatonin, administered to the rat in vivo and in vitro was able to offer neuroprotection by curtailing the production of superoxide radicals induced by rotenone. Mitochondria, being the major target of rotenone, the effects of melatonin were investigated at the mitochondrial level. Melatonin was able to increase the electron transport chain activity thus preventing the respiratory inhibition by rotenone. The pineal hormone also counteracted the action of rotenone on complex I enzyme. These results suggest melatonin's ability to potentially limit the free radical generation and thereby modulate the mitochondrial functions. The detection and measurement of lipid peroxidation is the evidence most frequently cited to support the involvement of free radical reactions in toxicology and in human disease. Melatonin also offered significant protection in vivo and in vitro against rotenone induced lipid peroxidation. Since iron plays a major role in oxidative damage and in the progression of Parkinson's disease, the effect of melatonin on both rotenone and iron induced lipid peroxidation was investigated, the results of which show that melatonin affords protection and this was suggested to be due to its interaction with the rotenone-iron complex that might have formed. Electrochemical studies were further used to characterise the interactions between melatonin, rotenone and iron (III). Melatonin was shown to bind with iron and thus reducing their toxicity. Histological studies were undertaken to assess the effects of melatonin on rotenone induced toxicity on the dopaminergic neurons in the rat brain. Rotenone treated brains showed extensive neuronal damage whereas with melatonin less damage was observed. Rotenone induces apoptosis via reactive oxygen species production and apoptotic cell death has been identified in PD brains. Furthermore, the apoptotic cell death was detected and quantified by the TUNEL staining. Rotenone treated sections showed signs of apoptosis whereas with melatonin, less apoptotic damage was observed. The findings of this study indicate that the neurohormone, melatonin may protect against rotenone-induced neurodegeneration. Since melatonin production falls substantially during ageing, the loss of this antioxidant is theorized to be instrumental in the degenerative processes associated with advanced age. Considering how devastating diseases such as Parkinson's disease, are to a patient and the patient's families, the discovery of protective agents are a matter of urgency. Further investigations using the pesticide model will help to determine the involvement of environmental exposure in the pathogenesis of human diseases as well as to test therapeutic strategies for the treatment of such diseases.
Keywords: Melatonin; Nervous system -- Degeneration -- Treatment; Rotenone